"I'm Trying to Stop Things Before They Happen": Carers' Contributions to Patient Safety in Hospitals. (August 2019) - Merner, Bronwen; Hill, Sophie; Taylor, Michael
Patient safety policies increasingly encourage carer (i.e., family or friends) involvement in reducing health care–associated harm in hospital. Despite this, carer involvement in patient safety in practice is not well understood—especially from the carers' perspective. The purpose of this article is to understand how carers of adult patients perceived and experienced their patient safety contributions in hospital. Constructivist grounded theory informed the data collection and analysis of in-depth interviews with 32 carers who had patient safety concerns in Australian hospitals. Results demonstrated carers engaged in the process of "patient-safety caring." Patient-safety caring included three levels of intensity: low ("contributing without concern"), moderate ("being proactive about safety"), and high ("wrestling for control"). Carers who engaged at high intensity provided the patient with greater protection, but typically experienced negative consequences for themselves. Carers' experiences of negative consequences from safety involvement need to be mitigated by practice approaches that value their contributions.